Analisis Efesiensi Strategi Manajemen Resiko Keuangan Terhadap Produk Asuransi Umum (Unit Syariah) Pada Pt Bumida Cabang Medan - Sri Ramadhani; Nuri Aslami; Ella Sri Wahyu Ningsih (Universitas 45 Surabaya, 2024)
This research aims to determine the Efficiency Analysis of Financial Risk Management Strategies for General Insurance Products (Sharia Units) at PT Bumida Medan Branch. In this research the research approach used is qualitative descriptive. Data collection was carried out using literature studies, namely theoretical studies, references and literature. other scientific research, the data analysis technique used in this research uses the Miles and Huberman model. The results of this research are the underwriter's way of minimizing the risks often faced by PT BUMIDA Medan branch in the service activities provided is by ensuring the objects that must be insured, the benefits What can be obtained if the implementation of risk management is carried out well and effectively to prevent failure so that profits can be increased or at least the company's losses are not too large. The aim of financial management is to maximize profits or profits and minimize costs in order to obtain a maximum return on decisions, in explaining the company towards development and running the company, the obstacles in risk management are 1) candidate morale. 2) honesty of insurance company marketing.